Forms of Address as Markers of Hierarchical Relations in Japanese and Indonesian Workplace Culture: A Contrastive Sociopragmatic Analysis - Mochamad Rizky Adriansyah; Teguh Santoso (Transpublika Publisher, 2026)
Language use is deeply embedded in social structures, with address terms serving as key markers of power relations, social distance, and politeness in interpersonal communication. In workplace settings, the choice of address terms reflects and reinforces hierarchical relations, yet the extent to which cultural norms shape this system varies across societies. This study examines the use of address terms as markers of hierarchical relations in Japanese and Indonesian workplace cultures through a contrastive sociopragmatic approach. The data were collected from professional interactions both formal and semi‑formal in workplace settings in Japan and Indonesia, complemented by observations and document analysis. The analysis focuses on the types of address terms, their social functions, politeness strategies, and the influence of cultural norms and interpersonal distance on their selection. The findings reveal that in Japanese workplace culture, occupational titles (such as buchō and kachō) and the systematic use of keigo including sonkeigo, kenjōgo, and teineigo serve to reinforce hierarchical structures and maintain workplace harmony (wa), often through negative politeness strategies that protect the superior’s “face.” In contrast, Indonesian workplace interactions employ address terms such as Bapak, Ibu, Pak, Bu, Mas, and Mbak to express respect and politeness, but with greater flexibility influenced by interpersonal closeness and local cultural norms. While both cultures use address terms to signal hierarchy and maintain politeness, Japanese practices are more formal and consistent, whereas Indonesian practices are more adaptable and egalitarian. This study contributes to cross‑cultural sociolinguistic research and offers insights for effective professional communication in multicultural work environments.